Computational analysis of probabilistic reversal learning deficits in male subjects with alcohol use disorder - Bağci, Başak; Düsmez, Selin; Zorlu, Nabi; Bahtiyar, Gökhan; Isikli, Serhan; Bayrakci, Adem; Heinz, Andreas; Schad, Daniel J.; Sebold, Miriam (Frontiers in Psychiatry, 2022)
Abstract Background: Alcohol use disorder is characterized by perseverative alcohol use despite negative consequences. This hallmark feature of addiction potentially relates to impairments in behavioral flexibility, which can be measured by probabilistic reversal learning (PRL) paradigms. We here aimed to examine the cognitive mechanisms underlying impaired PRL task performance in patients with alcohol use disorder (AUDP) using computational models of reinforcement learning. Methods: 28 early abstinent AUDP and 27 healthy controls (HC) performed an extensive PRL paradigm. We compared conventional behavioral variables of choices (perseveration; correct responses) between groups. Moreover, we fitted Bayesian computational models to the task data to compare differences in latent cognitive variables including reward and punishment learning and choice consistency between groups. Results: AUDP and HC did not significantly differ with regard to direct perseveration rates after reversals. However, AUDP made overall less correct responses and specifically showed decreased win-stay behavior compared to HC. Interestingly, AUDP showed premature switching after no or little negative feedback but elevated proneness to stay when accumulation of negative feedback would make switching a more optimal option. Computational modelling revealed that AUDP compared to HC showed enhanced learning from punishment, a tendency to learn less from positive feedback and lower choice consistency. Conclusions: Our data do not support the assumption that AUDP is characterized by increased perseveration behavior. Instead our findings provide evidence that enhanced negative reinforcement and decreased non-drug related reward learning as well as diminished choice consistency underlies dysfunctional choice behavior in AUDP.